COMMUNITY-BASED TELENURSING TRAINING ON STIMULATION, DETECTION, AND EARLY INTERVENTION OF CHILD GROWTH AND DEVELOPMENT (SDIDTK) FOR PAUD TEACHERS AND POSYANDU CADRES IN STUNTING PREVENTION - Anggarasari, Nandhini Hudha; Suhartini, Titin Suhartini; Firdaus, Rifsky Firda; Haepina, Haulah (Jurnal Al-Ijtimaiyyah, 2026)
This study addresses stunting as a multidimensional community development issue that requires collaborative efforts at the grassroots level. Stunting, caused by chronic malnutrition and recurrent infections during the first 1,000 days of life, remains a significant challenge in Indonesia. Strengthening the capacity of community-based actors such as PAUD teachers and Posyandu cadres is essential for early detection and prevention. However, their limited knowledge of early screening practices hinders effective intervention. This study aims to analyze and compare the capacity improvement of PAUD teachers and Posyandu cadres through community-based SDIDTK telenursing training. A quasi-experimental method with a non-equivalent control group design was employed. The sample consisted of active PAUD teachers and Posyandu cadres selected through purposive sampling, all of whom had access to digital devices for training. Data were analyzed using independent sample t-tests. The results showed no statistically significant difference between the two groups (p = 0.874). However, both groups experienced an increase in knowledge after the training. These findings indicate that SDIDTK telenursing training is effective as a community-based capacity-building approach and can equally empower different community actors in supporting early stunting detection.